Entrepreneurship, economic growth and policy in emerging economies - A. Roy Thurik (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Entrepreneurship has emerged as an important element in the organization of economies. This emergence did not occur simultaneously in all developed countries. Differences in growth rates are often attributed to differences in the speed with which countries embrace entrepreneurial energy. This led to the political mandate to promote entrepreneurship. Hence, a clear and organized view is needed of what the determinants and consequences of entrepreneurship are. The present contribution tries to provide this view with a particular view on emerging economies. Entrepreneurship, its drivers and its consequences can be best understood using the model of the entrepreneurial economy which explains the functioning of the modern economy. This model differs from that of the earlier managed economy. Policies in emerging economies should aim at combining the two models.
Keywords: L26; M13; O10; P5; 330; entrepreneurship; small firms; economic growth; economic development; policy; Entrepreneurship-Ansatz; Wirtschaftswachstum; Schwellenländer